Analisis Perilaku Termal dan Kapasitas Panas Mata Pahat Uncoated dan Coated Carbide pada Proses Pemotongan Besi Tuang - M. Sobron Yamin Lubis; Abrar Riza; Han Han; Nathan Ferdiantino Hidayat (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
During turning, most energy is converted into heat, which spreads to the cutting tool, chips, and workpiece. Heat transfer occurs via conduction and can cause tool wear. To reduce this, coatings with low thermal conductivity are used. This study aims to analyze heat absorption and heat capacity of uncoated carbide and TiCN + Al₂O₃ + TiN coated carbide tools during cast iron turning. Tests were conducted at 160, 210, and 260 m/min cutting speeds. Temperatures were measured using a K-type thermocouple placed at the tooltip. Results show the coating effectively reduces heat penetration into the tool. The coated carbide required 64.5 J/K for a 1 K temperature rise, while the uncoated only needed 1.5 J/K. This indicates uncoated tools heat up faster and wear more quickly.